Satisfaction with clinical pathway implementation versus job performance of clinicians: empirical evidence on the mediating role of work engagement from public hospitals in Sichuan, China - Junlong Li; Lu Ao; Jay Pan (BMC, 2024)
Abstract Background The job performance of clinicians is a clear indicator of both hospital capacity and the level of hospital service. It plays a crucial role in maintaining the effectiveness and quality of medical care. Clinical pathways are a systematic method of quality improvement successfully recommended by broader healthcare systems. Since clinicians play a key role in implementing clinical pathways in public hospitals, this study aims to investigate the effect of the satisfaction of clinicians in public hospitals with clinical pathway implementation on their job performance. Methods A cross-sectional study design was used. Questionnaires were administered online. A total of 794 clinicians completed the questionnaires in seven tertiary public hospitals in Sichuan Province, China, of which 723 were valid for analysis. Questionnaires contained questions on social demographic characteristics, satisfaction with clinical pathway implementation, work engagement, and job performance. Structural Equation Model (SEM) was used to test the hypotheses. Results The satisfaction of clinicians in public hospitals with clinical pathway implementation was significantly positively correlated with work engagement (r = 0.570, P < 0.01) and job performance (r = 0.522, P < 0.01). A strong indirect effect of clinicians' satisfaction with clinical pathway implementation on job performance mediated by work engagement was observed, and the value of this effect was 0.383 (boot 95%CI [0.323, 0.448]). Conclusion The satisfaction of clinicians in public hospitals with clinical pathway implementation not only directly influences their job performance, but also indirectly affects it through the mediating variable of work engagement. Therefore, managers of public hospitals need to pay close attention to clinicians' evaluation and perception of the clinical pathway implementation. This entails taking adequate measures, such as providing strong organizational support and creating a favorable environment for the clinical pathway implementation. Additionally, focusing on teamwork to increase clinicians' satisfaction can further enhance job performance. Furthermore, managers should give higher priority to increasing employees' work engagement to improve clinicians' job performance.